Reconstructing The Islamic Investment Fund Management Model Of Danantara: A Maqasid Al-Shariah And Shariah Compliance Analysis - Mahmud Yusuf Yusuf (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
The rapid expansion of the global Islamic finance industry has heightened the need for investment models that uphold not only formal Shariah compliance but also the higher objectives of Islamic law (Maqasid al-Shariah). This study critically examines the case of Danantara, an Islamic investment fund operating under a hybrid equity-debt structure, to assess the extent of its alignment with Maqasid al-Shariah principles particularly Hifz al-Mal (wealth preservation), ‘Adl (justice), and Maslahah (public welfare). The analysis reveals significant gaps in Danantara’s current model, including weak ethical diversification, inconsistent purification mechanisms for non-permissible income, and opaque fee structures that undermine transparency and justice. To address these deficiencies, the study proposes a reconstructed fund management model that integrates strengthened Shariah governance, mandatory third-party audits, and a shift toward positive-impact investments such as green sukuk and healthcare. It also recommends standardized disclosure practices for Shariah non-compliance and purification reporting to enhance investor trust. Guided by Jasser Auda’s systems approach to Maqasid al-Shariah and the compliance standards of AAOIFI and IFSB, this reconstructed model aims to bridge the gap between technical legality and ethical substance. The findings offer a practical blueprint for transforming Islamic fund governance and advancing the industry's contribution to social and environmental well-being.